Enhanced mechanical and thermal performance of multiwalled carbon nanotubes-filled polypropylene/natural rubber thermoplastic elastomers. (1st March 2021) - Nair, Sharika T.; Vijayan P., Poornima; George, Soney C.; Kalarikkal, Nandakumar; Thomas, Sabu
Abstract : This paper reveals the effect of the concentration-dependent migration of MWCNTs among blend components on the static, dynamic, mechanical and thermal properties of MWCNT-filled PP/NR blends. Abstract : The effects of multiwalled carbon nanotubes (MWCNTs) on the mechanical, dynamic and thermal properties of polypropylene/natural rubber (PP/NR) blends with two different blend compositions were studied. The observations were correlated with morphological attributes. A brittle to ductile transition was observed above a critical concentration of MWCNTs in PP/NR blends, and the required critical concentration depends on the blend composition. It was found that MWCNTs significantly improved the tensile toughness and impact strength of PP/NR blends of both compositions, especially at 5 wt% MWCNTs. The toughening effect of MWCNTs on PP/NR is more pronounced in composites with co-continuous morphologies (50PP/50NR) than that with matrix-droplet (80PP/20NR) morphologies. The dynamic mechanical analysis confirmed the existence of two glass transition temperatures corresponding to PP and NR phases. The increasing T g of NR phase with increasing MWCNT content indicates the preferential localization of MWCNTs in the NR phase of PP/NR blends. The thermal degradation behavior of developed nanocomposites determined by thermogravimetric analysis (TGA) showed that the thermal stability of nanocomposites was improved and their rate of degradation was reduced, which was attributed to the network-like structure formation of MWCNT in blends.